P02.07.B Patient-derived glioblastoma organoids: Elucidating the mechanisms of glioblastoma therapeutic resistance in the context of tumor microenvironment. (5th September 2022) - Habič, A; Majc, B; Porčnik, A; Bošnjak, R; Mlakar, J; Lah Turnšek, T; Breznik, B; Novak, M
Abstract: Background: Intratumoral heterogeneity plays an important role in glioblastoma (GB) resistance to standard therapy consisting of irradiation and chemotherapy with temozolomide (TMZ). However, classical in vitro GB models fail to represent the complex cellular composition of tumors in vivo, which hinders relevant examination of GB therapeutic response. To overcome these limitations, we studied the effects of irradiation and TMZ in a novel patient-derived organoid model. Material and Methods: We established a patient-derived GB organoid model by a protocol recently published by Jacob et al. Original tumor tissue and tissue-derived organoids were compared by immunofluorescence staining of selected cell type markers and qPCR analysis of expression levels of a panel of selected target genes, including 15 genes defining GB subtypes. To analyze GB therapeutic response, organoids from 11 patients were exposed to a single dose of irradiation (10 Gy), one-week treatment with TMZ (50 µM) or their combination. The effects of therapy were assessed by viability and invasion assays. Expression levels of a number of genes related to GB subtypes, epithelial-mesenchymal transition, stemness, DNA damage responses, cell cycle, cytokines, and cell markers of the tumor microenvironment (TME) were compared between treated organoids and untreated controls. In addition, the heterogeneity of the TME and its responses to treatment were investigated by spatially resolved transcriptomics with in situ sequencing (ISS) methodology. Results: Organoids recapitulate inter-patient variability and reflect the cellular composition and gene expression levels of the tumor tissue from which they were derived. GB stem cells and differentiated cancer cells are present in organoids along with various cells of the TME, e.g., macrophages and microglia, lymphocytes, and endothelial cells. Irradiation and TMZ showed no significant effects on organoid viability and invasion. However, some target genes were differentially expressed in the treated organoids, such as E3 ubiquitin-protein ligase MDM2 and cyclin-dependent kinase inhibitor 1A (CDKN1A). To our knowledge, we are the first to apply spatially resolved transcriptomics (ISS) to formalin-fixed, paraffin-embedded sections of (un)treated GB organoids. Our results elucidate the role of the TME in GB therapeutic response and shed light on potential mechanism underlying GB therapy resistance. Conclusion: Patient-derived GB organoids recapitulate the key characteristics and complex composition of patient's tumor tissue, providing a valuable platform for studies of GB therapeutic response and resistance.